2021
DOI: 10.1111/echo.14983
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with retrospective analysis of left ventricular function using clinical echocardiograms from a multicenter research study

Abstract: Background Retrospective multicenter research using echocardiograms obtained for routine clinical care can be hampered by issues of individual center quality. We sought to evaluate imaging and patient characteristics associated with poorer quality of archived echocardiograms from a cohort of childhood cancer survivors. Methods A single blinded reviewer at a central core laboratory graded quality of clinical echocardiograms from five centers focusing on images to derive 2D and M‐mode fractional shortening (FS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…This was the most common reason GLS as measured from three apical planes with 2D speckle tracking could not be determined in a previous GLS analysis. 23 This study suggests that A4LS can be used as a reasonable surrogate for GLS in retrospective analysis of CCS echocardiograms. in non-CCS adults.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…This was the most common reason GLS as measured from three apical planes with 2D speckle tracking could not be determined in a previous GLS analysis. 23 This study suggests that A4LS can be used as a reasonable surrogate for GLS in retrospective analysis of CCS echocardiograms. in non-CCS adults.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study from our group demonstrated that changes in CCS echocardiogram parameters are associated with development of clinical cardiomyopathy in pediatric patients 22 . However, in this retrospective case‐control study, only 10% of echocardiograms had adequate 2‐ and 3‐chamber apical views to assess GLS, limiting the ability to draw conclusions surrounding the predictive value of strain as measured by GLS 23 . Studies showing reduced GLS in this population have unsurprisingly also shown reduced apical 4‐chamber longitudinal strain (A4LS) measured from a single 2D apical plane as well 12,14,15,19 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, several limitations should be noted when interpreting these results: (a) The largest limitation is the retrospective nature of this study, which caused variability in available retrospective echocardiogram images and image quality. Although this limitation is not unique to our study and is common to retrospective imaging studies in this population, this hindered our ability to perform a Simpsons’ bi-plane measurement of ejection fraction [ 29 ]. Future studies utilizing cardiac magnetic resonance imaging should be considered to address this limitation.…”
Section: Discussionmentioning
confidence: 99%